MICROMORPHOLOGY CHARACTERIZATION POLLEN GRAINS OF SUBGENERA PRUNUS AND CERASUS (ROSACEAE) IN KURDISTAN REGION-IRAQ - Hasan, Ameena M.; Shahbaz, Saleem E.; Abdulrahman, Shamiran S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This investigation was aimed to study pollen grains of subgenera Prunus and Cerasus. The polleniferous materials were collected from different places of Kurdistan region of Iraq living specimens. Pollen grains of all investigated taxa of subgenera Prunus and Cerasus were isopolar, monad, symmetric, tricolporate, dicolporate and tetracolporate pollens also observed, but very rarely. The pollen grains shape of taxa of subgenera Prunus and Cecasus divided in two groups subprolate and prolate depending on P/E value.  While, the size were medium with the exception of P. domestica subsp. italica grains were found to be small in size. The percentage of repeat morphological shape of pollen grains in polar view showed that the triangular outlines shapes of pollen grains were the most repeated, while, in the equatorial view the elliptic outline shapes was dominant in all taxa. Pollen grains surface of studied taxa was showed striate pattern with perforations in the grooves except P. domestica subsp. insititia which appeared striate-reticulate type of exine sculpture. Principal component analysis can recognize 67.7 % of the total variability thus can help prediction of taxa.